Isothymia politik Cina : perjuangan orang Cina menuntut kesaksamaan - Firdaus Zainal, 1985-; Muhammad Din; Ismah Fauji (Kuala Lumpur : Ilham Books, 2023)
History of Chinese in Malaysia.
Includes bibliographical references.
Keywords: Political parties -- Malaysia; Chinese -- Malaysia -- Politics and government; Political culture -- Malaysia; Malaysia -- Politics and government